ANALYSIS OF PROCESSING METHODS FOR ZINC-CONTAINING INDUSTRIAL WASTES: A COMPREHENSIVE REVIEW (European Journal of Interdisciplinary Research and Development, 2025)
Zinc (Zn) is the fourth most produced metal globally, yet its extraction and recycling generate significant volumes of hazardous technogenic waste[1,2]. This article provides a comprehensive analysis of methods for recovering zinc from various industrial residues, including electric arc furnace dust (EAFD), Ni-Cd cakes, basic oxygen steelmaking (BOS) filter cakes, and zinc ferrites. Drawing on experimental data from the sources, we evaluate pyrometallurgical techniques such as carbothermic reduction in iron baths and reduction roasting, alongside hydrometallurgical flowsheet involving selective leaching and solvent extraction. Key findings indicate that while iron-bath processes achieve recovery rates exceeding 99.9%, hydrometallurgical routes offer superior selectivity for high-purity metal recovery[3]. The role of zinc ferrite (ZnFe2O4) as a primary barrier to recovery and mechanical insights into its decomposition are discussed.